Vocal communication of White-footed Tamarin (Saguinus leucopus) in the wild - Fuentes Jesualdo Arturo; Zerda-Ordóñez Enrique; Muñoz-Durán Joao (Caldasia)
The white-footed tamarin, Saguinus leucopus, is an endemic primate of Colombia whose vocal communication has been little studied. For a period of a month we applied behavior sampling with continuous record, recording tamarins’ vocalizations, and the behavioral contexts associated with them. The study took place at the “José Celestino Mutis” forest in Mariquita, Tolima department (Colombia). We compiled a vocal catalogue showing some acoustic properties of the vocalizations (i.e. duration and frequency). We identified 19 phonemes associated with different behavioral contexts. Young individuals emitted vocalizations of higher frequency than adults. We discuss the relevance of the tamarins’ acoustic displays on their social and ecological interactions